Allergic rhinitis: therapeutic strategies update Lactococcus lactis Plasma and tranilast–roxithromycin combination - Horiuchi, Yasuhiro (Allergologia et Immunopathologia, 2023)
* At present, there is no established definitive and reliable therapy for allergic rhinitis. * Combined effects of tranilast, which inhibits mast cell degranulation, and a specific macrolide antibiotic, roxithromycin, which has T helper 2 (Th2) cell inhibitory effects through ligands and receptors, may aid significantly in managing allergic rhinitis. * Lactococcus lactis strain Plasma (LC-Plasma) can induce plasmacytoid dendritic cells and consistent intake of LC-Plasma increases T helper 1 (Th1) responses, indicating a potential to suppress Th2 hypersensitivity conditions, such as allergic rhinitis. * A novel treatment approach for hay fever can now be chosen based on to the severity of the disease and amount of scattered pollen.